The Third Generation, or some of the Swan Songs of the Modern Movement - Capitel, Antón (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
There are significant similarities and differences between the architects born in 1918. Utzon always practised organicism, although in different versions; with the excessive organicism of the Sydney Opera House, he became Zevi’s model. Sáenz de Oíza worked from the rationalist recovery as “avant-garde”, towards an architecture that was closer to Team 10, and ended up in the organicism of the Torres Blancas project and the Banco de Bilbao. Rudolph was personal and eclectic. He received extraordinary attention from Zevi concerning his most celebrated work, the Yale Art and Architecture Building. Van Eyck, an essential figure of Team 10, criticised the sequels of the masters of the Modern Movement and tried to bring architecture closer to history, the city and anthropology. However, his brilliant work reached more independent values. All of them, including Zevi, represented the best of the architecture of their time, but also the end of the Modern Movement and the lack of paths to the future.